2002
DOI: 10.1002/mds.10111
|View full text |Cite
|
Sign up to set email alerts
|

Health‐Related quality of life in patients with advanced Parkinson's disease treated with deep brain stimulation of the subthalamic nuclei

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disorder for which there is as yet no cure. It affects many aspects of patients' lives, only some of which can be monitored by available clinical rating scales. In the past decade, there has been a new emphasis on the use of health-related quality of life (HRQOL) measures to describe patient response to treatment. We describe patient-reported HRQOL in subjects who underwent bilateral deep brain stimulation (DBS) of the subthalamic nuclei (STN) for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 19 publications
7
49
1
2
Order By: Relevance
“…Over the last years, when performed in experienced centers, STN-DBS is generally a safe and effective intervention, and different groups showed consistently improvement in cardinal motor manifestations of PD [8,12,13,19] and in global QoL regardless of the scale used, either generic (SF36) or specific scale (PDQ39) [7,16,20]. In our study, with a 12 month follow-up, STN-DBS was an overall effective intervention.With regard to QoL comparing our PDQ39 data to the results of Peto's study [21], our mean scores before surgery were similar to that of patients with ten years duration of disease.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Over the last years, when performed in experienced centers, STN-DBS is generally a safe and effective intervention, and different groups showed consistently improvement in cardinal motor manifestations of PD [8,12,13,19] and in global QoL regardless of the scale used, either generic (SF36) or specific scale (PDQ39) [7,16,20]. In our study, with a 12 month follow-up, STN-DBS was an overall effective intervention.With regard to QoL comparing our PDQ39 data to the results of Peto's study [21], our mean scores before surgery were similar to that of patients with ten years duration of disease.…”
Section: Discussionmentioning
confidence: 60%
“…Only few studies have already assessed the impact of STN-DBS on QoL [7,10,11,16,27]. Lagrange et al [10] assessed the impact of bilateral STN stimulation in 60 PD patients before and 12 months after surgery.…”
Section: Discussionmentioning
confidence: 98%
“…In most patients, DBS alleviates parkinsonian motor signs, shortens 'off' periods, and reduces druginduced dyskinesias, dystonia, and motor fluctuations (Rodriguez-Oroz et al, 2004;Anderson et al, 2005;Weaver et al, 2005;Portman et al, 2006;Bronstein et al, 2011). In general, both GPi-and STN-DBS are more effective than medical management alone to alleviate motor deficits in patients with advanced PD (Just and Ostergaard, 2002;Martinez-Martin et al, 2002;Troster et al, 2003;Lezcano et al, 2004;Diamond and Jankovic, 2005;Erola et al, 2005;Halbig et al, 2005;Lyons and Pahwa, 2005;Deuschl et al, 2006;Rodrigues et al, 2007a, b;Montel and Bungener, 2009;Weaver et al, 2009b;Zahodne et al, 2009). In contrast to patients with GPi-DBS, those with STN-DBS are often able to substantially reduce the medication doses (Breit et al, 2004; …”
Section: Current Surgical Targetsmentioning
confidence: 99%
“…Preliminary data are, nonetheless, encouraging. Not only do patients report significant improvements on disease-specific QOL questionnaires after STN-DBS [3,4], but such QOL improvements are discerned even in comparison to a PD control group on the waiting list for surgery and receiving optimal medical therapy [5]. The critical factors underlying QOL improvement remain to be elucidated, but Martí-nez-Martín et al [6] found that the percentage change in QOL (the PDQ-39 Summary Index) among 17 patients evaluated before and 6 months after surgery was related to the percent improvement in the right extremity Abnormal Involuntary Movement Scale score.…”
Section: Introductionmentioning
confidence: 99%